FACE-OFF : The Portrait in Recent Art - Feldman, Melissa E.; Buchloh, Benjamin H.D.; Joslyn Art Museum, Omaha; Weatherspoon Art Gallery, University of North Carolina, Greensboro (Philadelphia : Institute of Contemporary Art, University of Pennsylvania, 1994)
Antoni, Janine ; Boltanski, Christian ; Close, Chuck ; Coplans, John ; Faigenbaum, Patrick ; Goldin, Nan ; Hammons, David ; Kabakov, Ilya ; Katz, Alex ; Kilimnik, Karen ; Koons, Jeff ; Mapplethorpe, Robert ; Neel, Alice ; Oates, Daniel ; O'Grady, Lorraine ; Ray, Charles ; Richter, Gerhard ; Ruff, Thomas ; Serrano, Andres ; Sherman, Cindy ; Warhol, Andy ; Wilke, Hannah
FACE-OFF: The Portrait in Recent Art, Institute of Contemporary Art, University of Pennsylvania, Philadelphia, September 9 - October 30, 1994 ; Joslyn Art Museum, Omaha, Nebraska, January 28 - March 19, 1995 ; Weatherspoon Art Gallery, University of North Carolina, Greensboro, April 9 - May 28, 1995
boek